Long term effect of INTRABEAM single irradiation on the expression of miRNAs inMCF-7 cells. Issue 4 (December 2022) - Pan, Lingxiao; Huang, Zizhong; Zhan, Qianchao; Zhang, Xiaoshen; Tang, Wei; Zheng, Wenbo
Abstract: Intraoperative radiation (IORT) has been increasingly popular in recent years. INTRABEAM has been utilized to treat cancers in various regions of the body as a small intraoperative radiation device. Flat plate, surface, and needle applicators have also been developed by INTRABEAM to meet various irradiation parameters. However, there are still a few basic research on intraoperative radiation in INTRABEAM. The goal of this study was to see how single irradiation affected the expression of miRNAs in breast cancer cells over time. INTRABEAM, an intraoperative radiotherapy device, was used to irradiate MCF-7 cells with a single 6 Gy radiation dosage. Four weeks after the irradiations, high-throughput sequencing of miRNAs was performed. High-throughput sequencing revealed a change in miRNA expression profile four weeks after irradiation. hsa-miR-4485–3p, hsa-miR-215–5p, and hsa-miR-2276–5p were the top three up-regulated miRNAs. hsa-miR-6886–5p, miR-500-y, and miR-6544-x were the top three down-regulated miRNAs. After a single-dose irradiation of 6 Gy with the INTRABEAM device, significant differences in miRNA expression in MCF-7 cells could continue for a long period. INTRABEAM radiotherapy may have therapeutic effect on breast cancer by regulating mRNA expression.